(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
تم إجراء سلسلة من التجارب تضم مجموعتين، الأولى أجريت في درجة حرارة المختبر، والثانية في الحاضنة في الفترة ما بين أيلول وكانون الأول 2004. ومن أجل ذلك تم استزراع نوع العوالق الحيوانية Brachionus plicatilis المستخدم كغذاء ليرقات الأسماك وصغارها، بهدف التوصل إلى نوع الغذاء أو الخلائط الغذائية الأفضل، والذي يؤدي استخدامه إلى تحسين الإنتاجية (المردود) لهذا النوع المستزرع، ذي الانتشار الواسع في مجال الاستزراع البحري غذاءً حياً. استزرع أيضاً نوعان من العوالق النباتية هما: Nannochloropsis oculata و Tetraselmis suecica لاستخدامها كغذاء حي بشكل منفرد، ومن خلال خلائط غذائية مختلفة تضم طحين السمك وخميرة الخبز، بالإضافة إلى خميرة الخبز فقط بالنسبة للنوع B. plicatilis. تبين نتيجة التجارب أن استخدام خليط من الطحلب N.oculata أو T.suecica وطحين السمك أفضل بكثير من استخدام الطحالب بمفردها، أو مع خميرة الخبز، لأن خليط الطحلب مع طحين السمك يؤدي إلى زيادة الإنتاجية (المردود) للنوع (B.plicatilis ) بـ (4-10) أضعاف وسطياً. وتلعب درجة الحرارة دور العامل الرئيسي والمحدد (في حال توفر كمية الغذاء الكافية) بالنسبة لتكاثر ونمو، وزيادة عدد أفراد النوع المستزرع، حيث درجة الحرارة المناسبة لتكاثره ونموه هي ما بين (26 و 30° م) وسطياً. A series of experiments which include two groups have been carried out. The first is executed at the laboratory temperature, the second is in the incubator in the period between September and December in 2004. Therefore, this zooplankton species Brachionus plicatilis, used as food for fish larvae and small fish, is cultivated in order to obtain the best kind of food or nutrient mixtures. So using it will lead to improve the productivity (outcome) of this culture species, which is widespread in the field of Mariculture as a live food . Two species of phytoplankton have been cultivated: Nannochloropsis oculata and Tetraselmis suecica are cultivated in order to use them separately as live food. Also through different nutritive mixtures contain baker’s yeast and fish meal, in addition to the baker’s yeast only according to species B.plicatilis. As a result of the expriments, it is obvious that using a mixture of algae N.oculata, or T. suecica and fish meal is much better than using just algae or with the baker’s yeast, because the mixture of algae with the fish meal leads to increase of productivity (outcome) of the species B.plicatilis about 4-10 times as average. The temperature plays a role of the main and defined factor (in the case of the abundance of sufficient food quantity) according to the reproduction and growth. Consequently, the increase greatly in number of individuals of species which is cultivated, so the temperature, that is suitable for its reproduction and growth is between 26-30° C as average.